ANALISIS PENINGKATAN KASUS PERCERAIAN DIMASA PANDEMI COVID-19 (Studi Peningkatan Gugatan Perceraian di Pengadilan Agama Jakarta Timur) - Muhammad Yusuf Muda Azka (2022)
The Covid-19 pandemic has led to a change in the order of life in the family, caused by the decline of the economy as a result of social activity restriction policies. This policy was issued by the government in order to suppress the spread of cases of Covid-19 sufferers in Indonesia. Social restriction policies not only limit people's activities personally, but also limit business activities in all sectors. This led to the closure of business activities so that the company was forced to lay of workers while even laying of permanently. The cessation of business activities has an impact on the decline of people's income significantly, and eventually disrupts the family economy. With the disruption of the family economy, causing house hold harmony is disrupted and eventually divorce occurs. Divorce cases duringtheCovid-19 pandemic increased sharply, especially divorce lawsuits filed by wives. This article is based on the number of divorce cases during the Covid-19 pandemic that occurred in the DKI Jakarta province, especially at the East Jakarta Religious Court. The issues in this article are about the reasons for filing a divorce lawsuit in the early period of the Covid-19 pandemic and the considerations of the East Jakarta Religious Court Judge in deciding on the divorce lawsuit during the COVID - 19 pandemic. This study is a socio-legal study with data sources obtained online and of line, as well as direct explanations from competent informants. The data is analyzed descriptively analytically with a qualitative approach. The object of the study is a divorce lawsuit in the East Jakarta Religious Court with data samples at the end of 2019-2020. The results of the study showed that the reasons for filing divorce lawsuits, most of which were filed by the wife, were family economic issues, as well as juridical, sociological, and psychological considerations that became the basis of judges in granting and deciding divorces.